KOMPETENSI PUSTAKAWAN DALAM LAYANAN REFERENSI VIRTUAL : MENYOAL PERAN PUSTAKAWAN SEBAGAI ”KNOWLEDGE WORKER” - Falih Ijlal Septian; Yunus Winoto (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2025)
The emergence of virtual reference services in library institutions is inseparable from the developments in information technology that have occurred in society over the last few decades. The purpose of this study is to determine librarian competencies in providing virtual reference services. Virtual reference service itself is defined as a service that utilizes information technology and various social media platforms to fulfill users' information needs, allowing them to seek information sources without having to physically visit the library. Based on the results of the study, it was revealed that librarians must possess two main competencies: 1) professional competence, such as knowledge and skills in using information technology, utilizing information sources, and accessing resources to serve users; and 2) personal competence, which relates to communication skills, attitudes, and insights possessed by reference librarians. To achieve an optimal virtual reference service, these two competencies must be an integral part of reference librarians.